Understanding financialization: Standing on the shoulders of Minsky - Charles Joseph Whalen (e-Finanse: Financial Internet Quarterly, 2017)
Since Hyman Minsky's death in 1996, much has been written about financialization. This article - by means of the synthesis, interpretation, and assessment of an extensive literature - explores the issues that Minsky examined in the last decade of his life and considers their relationship to the financialization literature. At the heart of those issues is what Minsky called money manager capitalism, which he viewed through the lens of a theory of capitalist development inherited from Joseph Schumpeter. Advancing our understanding of the history of financial economics, the article shows how Minsky contributed to - indeed, anticipated much of - the study of financialization. The article also identifies two sources of Minsky's insightfulness: his treatment of economics as a grand adventure, and his willingness to step beyond the world of theory and interact with the world of practice. Today, scholars with a Minsky perspective face formidable challenges, but, the author concludes, within Minsky's writings is also a glimmer of hope: Economic systems are not natural systems; we can reshape them to achieve a more humane world.
Keywords: B26; 330; Hyman Minsky; money manager capitalism; financialization